Solution chemistry-based nano-structuring of copper dendrites for efficient use in catalysis and superhydrophobic surfaces - Bakthavatsalam, Rangarajan; Ghosh, Subrata; Biswas, Ratul Kumar; Saxena, Aayushi; Raja, Alagar; Thotiyl, Musthafa Ottakam; Wadhai, Sandip; Banpurkar, Arun G.; Kundu, Janardan (RSC Advances, 2016)
Despite their performance and economic advantages over Ag and Au, there have been no focused research efforts on the nano-structuring of Cu dendrites with respect to fine-tuning their structure/morphology towards the efficiency enhancement of suitable applications. Reported here is a simple, versatile, environmentally-friendly and galvanic replacement reaction-based solution chemistry methodology to synthesize highly nano-structured copper dendrites targeted towards the efficiency enhancement of desired applications. Herein, copper is deposited galvanically on an Al foil in the presence of NaCl/HCl, wherein the chloride anions augment an uninterrupted replacement reaction. The growth process of Cu dendrites has been probed in detail. The presence of acid, the type of Cu2+ precursor salt, the Cu2+ ion concentration, the surfactant concentration and the reaction temperature are all demonstrated to provide useful means of modulating the surface structure/morphology of the dendrites. Notably, dendrites formed in the presence of acid are found to be highly nano-structured. Moreover, it is also found that the morphology/structure of the obtained Cu deposit depends considerably upon the choice of the Cu2+ precursor salt, a parameter that has been completely overlooked in the past. The acid-induced nano-structuring of the dendrites is exploited for enhancing their efficiency in the catalytic reduction of para-nitrophenol and for fabricating self-cleaning superhydrophobic surfaces. These nano-structured dendrites are demonstrated to have the highest ever normalized rate constant for the catalytic reduction reaction. Superhydrophobic surfaces fabricated using these dendrites demonstrate excellent self-cleaning abilities, showing a high contact angle (159 degrees) with low contact angle hysteresis (2 degrees). This facile synthetic strategy for the fabrication of highly nano-structured Cu dendrites is expected to open up avenues for the production of Cu-based low-cost functional nano/micro-materials.

Facile synthesis and self-cleaning application of bimetallic (CuSn, CuNi) dendrites - Biswas, Anupam; Kulkarni, Mayuresh A.; Bakthavatsalam, Rangarajan; Mondal, Sourik K.; Dwivedi, Pravin K.; Shelke, Manjusha V.; Devi, Radhamonyamma N.; Banpurkar, Arun G.; Kundu, Janardan (Chemistryselect, 2017)
Bimetallic dendrites (Au, Ag, Pt, Pd) have received intense research interest due to their applications in catalysis and sensing. However, reports on rational synthesis of non-noble bimetallic dendrites that finds self-cleaning applications are scanty. Here, we demonstrate one step co-reduction based galvanic replacement reaction (GRR) for synthesis of alloyed bimetallic dendrites (CuSn, CuNi) with controlled surface roughness and chemical composition. Probing their growth process reveals that i) for CuSn dendrites, co-reduction of Cu2+ and Sn2+ is observed throughout GRR; ii) for CuNi dendrites, Cu nanoparticle, that deposits initially, augments the reduction of Ni2+ which leads to CuNi alloy phase formation during later stages of GRR. These dendrites, naturally having dual degree of surface roughness (micro/nano), have been exploited here for fabricating superhydrophobic surfaces (SHS) with excellent self-cleaning abilities. They show enabling properties such as high contact angle, minimal contact angle hysteresis, and excellent Cassie state stability with no impalement. They maintain superhydrophobicity when exposed to different environmental conditions (low temperature, high temperature, exposure to corroding solutions and UV radiation). The present facile methodology for fabrication of bimetallic dendrites is beneficial for low-cost production of functional nano/micro-materials.

Galvanic replacement-based Cu2O self-templating strategy for the synthesis and application of Cu2O–Ag heterostructures and monometallic (Ag) and bimetallic (Au–Ag) hollow mesocages - Bakthavatsalam, Rangarajan; Kundu, Janardan (Crystengcomm, 2017)
Polyhedral Cu2O microparticles as self-templates have been well-demonstrated for the synthesis of Cu2O–M heterostructures (M = Au, Pd, Pt) and Au nano/mesocages utilizing the galvanic replacement reaction (GRR) strategy. However, reports on GRR-based fabrication of Cu2O–Ag heterostructures and the ensuing Ag mesocages are scanty. There is no report that describes the phenomenon of facet selectivity during the GRR-based deposition of Ag on Cu2O template particles. Here, we have identified the underlying rationale behind the observed difficulty in nucleating Ag nanoparticles on an octahedral Cu2O self-template particle. Utilization of an appropriately chosen surfactant/complexant for the silver precursor helps in demonstrating the successful fabrication of Cu2O–Ag heterostructures (octahedral, cubic) with a tunable loading density of Ag NPs on the Cu2O surfaces. This is achieved using Cu2O template particles that undergo GRR with silver nitrate in the presence of nitric acid, and 5-sulfosalicylic acid as the surfactant (key role players). We provide evidence that supports facet selectivity during the deposition of Ag NPs on Cu2O cuboctahedral particles. Hollow octahedral Ag and Au–Ag bimetallic mesocages are fabricated that have rough surfaces, uniform morphology, and excellent shape retention. The fabricated heterostructures and mesocages act as an excellent SERS substrate. This is the first report on the rational synthesis of octahedral Cu2O–Ag heterostructures and octahedral hollow metallic mesocages utilizing the Cu2O self-templating strategy along with the demonstration of facet selectivity of Ag deposition on Cu2O template particles through GRR. The current approach offers a facile and versatile protocol for the synthesis of Cu2O–metal heterostructures and hollow noble metal mesocages.

Colloidal Mn2+ doped 2D (n =1) lead bromide perovskites: efficient energy transfer and role of anion in doping mechanism - Haris, Muhammed; Bakthavatsalam, Rangarajan; Kundu, Janardan (ChemistrySelect, 2018)
Mn²⁺ doping directly into APbCl3 type 3D nanocrystals, manifesting host to dopant energy transfer, have been heavily reported for illumination and display applications. However, these doped 3D ABX3 systems have low/modest exciton binding energy. Strongly bound excitons in the doped system can enhance the dopant‐host carrier exchange interactions leading to efficient energy transfer. Reported here is a simple and facile synthesis of colloidal Mn²⁺ doped (Butylammonium/octylammonium)2PbBr4 2D (n=1) perovskites that demonstrate enhanced energy transfer from strongly bound excitons of the host material to the Mn²⁺ dopant ions resulting in intense orange‐yellow emission due to spin forbidden internal transition (⁴T1 → ⁶A1) with the highest quantum yield (Mn²⁺) of 36%. Consistent with experimental evidences presented here, mechanism of this thermally aided doping process in these 2D systems, very likely, involves halide vacancy and its diffusion that precedes the cation exchange (doping) process. Owing to the high quantum yield, stability in ambient atmosphere, simplicity and scalability of the synthetic procedure, Mn²⁺ doped 2D perovskites could be beneficial as color converting phosphor material and can be utilized to further explore their magneto‐optoelectronic properties.

Synthetic control on structure/dimensionality and photophysical properties of low dimensional organic lead bromide perovskite - Haris, Muhammed P. U.; Bakthavatsalam, Rangarajan; Shaikh, Samir; Kore, Bhushan P.; Moghe, Dhanashree; Gonnade, Rajesh G.; Sarma, D. D.; Kabra, Dinesh; Kundu, Janardan (Inorganic chemistry, 2018)
Low dimensional lead halide perovskites have attracted huge research interest due to their structural diversity and remarkable photophysical properties. The ability to controllably change dimensionality/structure of perovskites remains highly challenging. Here, we report synthetic control on structure/dimensionality of ethylenediammonium (ED) lead bromide perovskite from a two dimensionally networked (2DN) sheet to a one dimensionally networked (1DN) chain structure. Intercalation of solvent molecules into the perovskite plays a crucial role in directing the final dimensionality/structure. This change in dimensionality reflects strongly in the observed differences in photophysical properties. Upon UV excitation, the 1DN structure emits white light due to easily formed “self-trapped” excitons. 2DN perovskites show band edge blue emission (∼410 nm). Interestingly, Mn2+ incorporated 2DN perovskites show a highly red-shifted Mn2+ emission peak at ∼670 nm. Such a long wavelength Mn2+ emission peak is unprecedented in the perovskite family. This report highlights the synthetic ability to control the dimensionality/structure of perovskite and consequently its photophysical properties.

Efficient broad-band emission from contorted purely corner-shared one dimensional (1D) organic lead halide perovskite - Biswas, Anupam; Bakthavatsalam, Rangarajan; Shaikh, Samir R.; Shinde, Aparna; Lohar, Amruta; Jena, Satyam; Gonnade, Rajesh G.; Kundu, Janardan (Chemistry of Materials, 2019)

Temperature-dependent photoluminescence and energy-transfer dynamics in Mn2+-doped (C4H9NH3)(2)PbBr4 two-dimensional (2D) layered perovskite - Bakthavatsalam, Rangarajan; Biswas, Anupam; Chakali, Madhu; Bangal, Prakriti Ranjan; Kore, Bhushan P.; Kundu, Janardan (Journal of Physical Chemistry C, 2019)
Reported here are the low-temperature photoluminescence (PL), energy-transfer mechanism, and exciton dynamics of Mn2+-doped two-dimensional (2D) perovskites that show interesting differences from their three-dimensionally doped counterpart. Dopant emission in 2D system shows increased PL intensity and shortened lifetime with increase of temperature and strong dopant emission even at low temperatures. Transient absorption (TA) spectroscopy reveals the dominant role of ``hot'' excitons in dictating the fast energy-transfer timescale. The operative dynamics of the generated hot excitons include filling up of existing trap states (shallow and deep) and energy-transfer channel from hot excitons to dopant states. Global analysis and target modeling of TA data provide an estimate of excitons (hot and band edge) to a dopant energy-transfer timescale of similar to 330 ps, which is much faster than the band edge exciton lifetime (similar to 2 ns). Such fast energy-transfer timescale arises due to enhanced carrier exchange interaction resulting from higher exciton confinement, increased covalency, and involvement of hot excitons in the 2D perovskites. In stark contrast to three-dimensional systems, the high energy-transfer rate in 2D system results in high dopant emission intensity even at low temperatures. Increased intrinsic vibronic coupling at higher temperatures further supports efficient Mn2+ sensitization that ultimately dictates the observed temperature dependence of the dopant emission (intensity, lifetime).

Ligand structure directed dimensionality reduction (2D -> 1D) in lead bromide perovskite - Bakthavatsalam, Rangarajan; Haris, Muhammed P. U.; Shaikh, Samir R.; Lohar, Amruta; Mohanty, Ashutosh; Moghe, Dhanashree; Sharma, Shivani; Biswas, Chinmoy; Raavi, Sai Santhosh Kumar; Gonnade, Rajesh G.; Kundu, Janardan (Journal of Physical Chemistry C, 2020)
Low dimensional (2D, 1D) lead halide perovskites are currently attracting huge research interest due to their enabling properties. Demonstrating synthetic control on the dimensionality/ structure of these perovskites is highly challenging. Dimensionality in these perovskites is largely dictated by the nature/structure and composition of the incorporating ligands and the utilized synthetic conditions. Here, we demonstrate chemical composition based control on reduction of dimensionality (2D -> 1D) for lead bromide perovskite utilizing 2-(2-aminoethyl)isothiourea dihydrobromide as a common precursor ligand (Isothio Bromide). Controlling the hydrothermal reaction parameters (temperature, time) at a fixed precursor ratio affords corner-shared, contorted 2D sheet perovskite and corner-shared, contorted, chiral 1D chain perovskite. Such dimensionality reduction leads to contrasting photophysical properties: 1D chain perovskite shows long-lived and self-trapped broad band emission, whereas 2D perovskite shows short-lived, band edge emission with a long tail. Mechanistic studies and single crystal structure analysis reveal the incorporation of the utilized precursor ligand (Isothio Bromide) in 2D perovskite. Surprisingly, the 1D perovskite is found to be chiral (P2(1) space group) incorporating 2-(2-aminoethyldisulfanyl)ethanamine and ammonium ions as the achiral ligands generated in situ due to hydrothermal cleavage of the precursor (Isothio Bromide) ligand. Such structural and compositional change of the ligands, which manifests a different hydrogen bonding network in the resultant perovskite structure, plays a decisive role in dictating the final molecular formula and dimensionality/structure of the perovskite which largely controls their photophysical properties.

Lead-free zero dimensional tellurium(iv) chloride-organic hybrid with strong room temperature emission as a luminescent material - Biswas, Anupam; Bakthavatsalam, Rangarajan; Bahadur, Vir; Biswas, Chinmoy; Mali, Bhupendra P.; Raavi, Sai Santosh Kumar; Gonnade, Rajesh G.; Kundu, Janardan (Journal of Materials Chemistry C, 2021)
Despite the current progress in `Pb-free' low dimensional main group metal halide based luminescent materials, it is challenging to synthesize Te(iv) halide hybrids with strong ambient emission with excitation features in the visible range as efficient and stable phosphors for potential lighting applications. Reported here is a (benzyltriethylammonium)(2)TeCl6 zero dimensional hybrid material with excitation features in the visible range and strong room temperature, broadband, intrinsic luminescence (PLQY similar to 15%) arising due to self-trapped excitons (STEs). Furthermore, a proof-of-concept LED architecture demonstrates successful optical down-conversion with a visible light excitation source. Here, exclusive adoption of a `regular' octahedral Te(iv)-halide unit structure with minimal static distortion provides a unique opportunity to unmask the role played by 5s(2) lone pair electrons in shaping the emissive properties. This effort may open up new avenues towards unravelling the role of lone pair stereoactivity in controlling the PLQY in low dimensional hybrids that has proven to be challenging for the reported (Sb, Sn) based low dimensional 5s(2) metal halide hybrid materials.

Metal halide structure and the extent of distortion control the photo-physical properties of luminescent zero dimensional organic-antimony(iii) halide hybrids - Biswas, Anupam; Bakthavatsalam, Rangarajan; Mali, Bhupendra P.; Bahadur, Vir; Biswas, Chinmoy; Raavi, Sai Santosh Kumar; Gonnade, Rajesh G.; Kundu, Janardan (Journal of Materials Chemistry C, 2021)
Antimony(iii) halide based zero dimensional hybrids have gained attention as broadband emitters. Until now, quadrangular pyramidal SbX5 based and octahedral SbX6 based 0D hybrids have been reported utilizing different organic ligands demonstrating some structural tunability affecting their emissive properties. Utilizing a common organic ligand, here we demonstrate the structural tunability (quadrangular pyramidal, octahedral, or a combination thereof) of the metal halide unit in Sb(iii)Cl 0D hybrids with contrasting photo-physical properties (broadband, Stokes shift, strong/weak colored emission). The structure-property-mechanism correlation of the synthesized compounds [1 (C12H52Cl18N8O4Sb3; tris Sb green); 2 (C12H50Cl14N8O3Sb2; tris Sb red); 3 (C24H88Cl25N16O4Sb3; tris Sb yellow)] identifies crucial factors that control their emissive properties. The X-ray analysis reveals the structure (1-octahedral; 2-quadrangular pyramidal; 3-combination thereof) and the order of the extent of structural distortion as 1-3 MUCH LESS-THAN 2. The metal halide coordination environment asymmetry and its structure are observed to dictate PL emission energy (1-green; 2-red; 3-yellow) as supported by a qualitative Molecular Orbital scheme. The extent of structural distortion guides the observed Stokes shifts (1-165 nm; 2-290 nm; 3-200 nm; 1-3 < 2). Interestingly, the extent of distortion is found to be well correlated with the observed PLQY (1-45%; 2-6%; 3-43%; 1-3 >> 2). This report clearly demonstrates the structural tunability and the effect of the metal halide unit structure/distortion in shaping the emissive properties of 0D organic Sb(iii) halide hybrids.

Synergistic electronic coupling/cross-talk between the isolated metal halide units of zero dimensional heterometallic (Sb, Mn) halide hybrid with enhanced emission - Biswas, Anupam; Bakthavatsalam, Rangarajan; Das, Deep K.; Sam, Jisvin; Mali, Bhupendra P.; Biswas, Chinmoy; Maana, Narugopal; Thomson, Stuart; Raavi, Sai Santosh Kumar; Kurungot, Sreekumar; Gonnade, Rajesh G.; Dutta, Sudipta; et al. (Journal of Materials Chemistry C, 2021)
Heterometallic 0D metal halide hybrids, consisting of more than one kind of metal halide units, are anticipated to manifest synergistic effects on the photo-physical properties of the constituent metal halide units. Such architectures hold great promise for design and development of function-targeted materials. However, heterometallic 0D hybrids, featuring isolated metal halide units, typically do not show any synergistic effects due to large inter-unit spatial separations that inhibit interactions/coupling between the constituent metal halide units. It remains challenging to design synthetic strategies that would support structural modifications to allow synergistic electronic coupling between the metal halide units in heterometallic 0D hybrids. Here, we report synthesis and characterization of heterometallic (Sb, Mn) 0D hybrid, namely Tris SbMnCl, with isolated MnCl5 units, (Sb/Mn)Cl-6 units, dispersed in the organic ligand matrix and layer of dynamic and networked water molecules. Steady state and time resolved emission spectra (TRES) analysis suggests strong synergistic interaction between the isolated metal halide units. Efficient energy transfer from the strongly absorbing Sb centres to emissive Mn centres results in the observed enhanced emission. Proton conductivity measurements together with first-principles calculations suggest the unique role of the networked water molecules in mediating the electronic coupling/energy transfer between the separated metal halide units in Tris SbMnCl hybrid. This report highlights the role of structure/composition of the synthesized heterometallic 0D hybrid in attaining electronic dimensionality higher than 0D through synergistic electronic interaction between the isolated metal halide units.

Controlled modulation of the structure and luminescence properties of zero-dimensional manganese halide hybrids through structure-directing metal-ion (Cd2+ and Zn2+) centers - Das, Deep Kumar; Bakthavatsalam, Rangarajan; Anilkumar, Vishnu; Mali, Bhupendra P.; Ahmed, Md Soif; Raavi, Sai Santosh Kumar; Pallepogu, Raghavaiah; Kundu, Janardan (Inorganic Chemistry, 2022)
Zero-dimensional (0D) metal halide hybrids with high exciton binding energy are excellent materials for lighting applications. Controlling/modulating the structure of the con-stituent metal halide units allows tunability of their photo-luminescence properties. 0D manganese halide hybrids are currently attracting research efforts in lighting applications due to their eco-friendly and strong emission. However, structural transformation-induced tunability of their photophysical propertieshas rarely been reported. Herein, we demonstrate a rationalsynthetic strategy to modulate the structure and luminescenceproperties of 0D Mn(II) halide hybrids utilizing the structure-directing d10metal ions (Cd2+/Zn2+). 0D metal halide hybrids ofCd2+/Zn2+, which act as hosts with tunable structures, accept Mn2+ions as substitutional dopants. This structural flexibility of thehost d10metal ions is realized by optimizing the metal-to-ligand ratio (Cd/AEPip). This reaction parameter allows structuraltransformation from an octahedral (AEPipCdMnBrOh) to a tetrahedral (AEPipCdMnBrTd) 0D Mn halide hybrid with tunableluminescence (orange -> green) with high photoluminescence quantum yield. Interestingly, when Zn2+is utilized, a tetrahedralAEPipZnMnBr structure forms exclusively with strong green emission. Optical and single-crystal X-ray diffraction structural analysisof the host and the doped system supports our experimental data and confirms the structure-directing role played by Cd2+/Zn2+centers. This work demonstrates a rational strategy to modulate the structure/luminescence properties of 0D Mn(II) halide hybrids, which can further be implemented for other 0D metal halide hybrids

Rational design of zero-dimensional manganese(II) halide hybrids with suppressed melting temperatures - Singh, Shivangi; Marayathungal, Jumana Hasin; Das, Deep Kumar; Khan, Akram Aadil; Bakthavatsalam, Rangarajan; Hathwar, Venkatesha R.; Kundu, Janardan (JOURNAL OF PHYSICAL CHEMISTRY C, 2024)
Keywords: ORGANIC-INORGANIC PEROVSKITES; TRANSITION